Uma abordagem para análise de desempenho e eficiência energética em dispositivos embarcados com uso do Asterisk. - MENEZES, Adauto Cavalcante (2018)
Voice over IP (VoIP) communication will dominate the computing world for years to come. To perform VoIP transmission, it is necessary to encode and decode the voice. This process consumes the major computing resources, such as processor and memory. The telecommunication industries provide equipment with high values, which makes access to this technology still very restricted. Embedded devices run systems with high criticality complex. Free voice over IP communication software Asterisk has as main function to implement all the functionalities of a telephone exchange. This is a viable alternative to use on embedded devices. These technologies promise to reduce costs and maximize results. This dissertation performs a performance analysis on three modern embedded devices (Raspberry Pi 3, Orange Pi Plus 2 and Banana Pi M3) using the Asterisk voice over IP communication system. The performance analysis consists in measuring the jitter, delay and bandwidth, as well as the quantitative simultaneous calls supported in each device with the SIP and IAX2 protocols with CODEC’s G.711a, G.711u, Gsm, Speex, Ilbc, G. 722, and in parallel, monitor the consumption of RAM, processing and power. The results show that the Raspberry Pi 3 and Banana Pi M3 devices satisfactorily support approximately 300 concurrent calls with memory consumption, processing, and moderate power. However, the Orange Pi Plus 2 device did not perform satisfactorily in the processing consumption.